2017
DOI: 10.1038/nn.4647
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytes control synaptic strength by two distinct v-SNARE-dependent release pathways

Abstract: Communication between glia cells and neurons is crucial for brain functions, but the molecular mechanisms and functional consequences of gliotransmission remain enigmatic. Here we report that astrocytes express synaptobrevin II and cellubrevin as functionally non-overlapping vesicular SNARE proteins on glutamatergic vesicles and neuropeptide Y-containing large dense-core vesicles, respectively. Using individual null-mutants for Vamp2 (synaptobrevin II) and Vamp3 (cellubrevin), as well as the corresponding comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(71 citation statements)
references
References 50 publications
3
68
0
Order By: Relevance
“…Recent demonstrations that parallel gliotransmission pathways can exist within single astrocytes (Schwarz et al, 2017) lend support to the notion that multiple signaling pathways are available to enable flexible interactions with neurons under different conditions.…”
Section: Discussionmentioning
confidence: 89%
“…Recent demonstrations that parallel gliotransmission pathways can exist within single astrocytes (Schwarz et al, 2017) lend support to the notion that multiple signaling pathways are available to enable flexible interactions with neurons under different conditions.…”
Section: Discussionmentioning
confidence: 89%
“…We found that CNO treatment in DVC::GFAP hM3Dq mice decreased food intake and induced c‐FOS expression in neighboring neurons; however, the underlying molecular mechanisms by which this occurs remain to be resolved. Astrocytes can modulate the activity of neurons by mechanisms including altered glutamate transport and also via release of neuroactive molecules (e.g., glutamate, ATP, d ‐serine) (Araque et al, ; Gourine et al, ; Matott, Kline, & Hasser, ; Panatier et al, ; Papouin, Dunphy, Tolman, Dineley, & Haydon, ; Schwarz, Zhao, Kirchhoff, & Bruns, ). Critically, glutamatergic signaling is the principal mechanism for communication between the vagus and second‐order NTS neurons (Doyle & Andresen, ) and NTS astrocytes directly sense vagal glutamate release via Ca 2+ ‐permeable AMPA receptors expressed on the cell membrane (McDougal et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of intracellular vesicles containing glutamate, VGLUTs 1 and 2 as well as specific vesicular proteins (v-SNAREs), were described in astrocytes by several research teams (Bezzi et al, 2004;Montana et al, 2004;Ni and Parpura, 2009;Bergersen et al, 2012). Recently, using single and double v-SNARE knockout mice, Schwarz et al (2017) have proven that astrocytes express synaptobrevin II and cellubrevin on distinct vesicle populations and mediate glutamate and neuropeptide Y release through distinct, previously unrecognized, secretion pathways which may be essential in neuron-astrocyte communication. Different experimental strategies that demonstrate a functional role of vesicular release from astrocytes were summarized by Bohmbach et al (2018).…”
Section: Astrocytes Add Significantly To Glutamate Excitotoxicitymentioning
confidence: 99%